Eloria subapicalis (Lepidoptera: Noctuidae: Lymantriinae) : rare and specialist species on Erythroxylum (Erythroxylaceae) in the cerrado - Diniz, Ivone Rezende (2011)
Eloria subapicalis (Walker, 1855) is a rare species (61 individuals in four years of samplings) of Noctuidae (Lymantriinae) with a specific diet consisting of leaves of Erythroxylum P. Browne (Erytroxylaceae) species in Brasilia’s cerrado. Generally, the rarity of a caterpillar species may have many explanations such as a generalist diet, being restricted to a host plant that is scarce in the area, or occurring in a limited geographical area. However, all the above explanations do not apply to E. subapicalis because it shows specificity of diet, uses a common host plant in the cerrado areas, and has a large geographical distribution.